‘You grow with the allergy’: a grounded theory study of families’ experiences with food allergy risk or diagnosis in early childhood - Christian Apfelbacher; Susanne Brandstetter; Julia Weigt; Madlen Hörold; Katharina Gerhardinger; Mara König; Magdalena Rohr (BMJ Open)
Objective Childhood food allergy is increasing in western societies. Preventing and managing food allergies is therefore essential for both parents and children. Given the limited previous research on parents’ experiences of food allergy prevention in early childhood, this study aimed to develop a grounded theory to understand the experiences and interactions of families whose children are at risk of, or have been diagnosed with, food allergy.Design Using a constructivist grounded theory approach, we used initial, focused and theoretical coding, as well as constant comparative analysis and memoing to interpret our data.Setting Thematic interviews were conducted in Germany between March and September 2022.Participant We included 28 carers (25 mothers and 3 fathers) of children aged 0–3 years diagnosed with food allergy or at risk of food allergy. We recruited participants using snowball and theoretical sampling.Results We developed a theory that we named ‘negotiating uncertainty in childhood food allergy’. This theory describes the experiences and interactions of families with a child at risk or diagnosed with food allergy with the central phenomena of negotiation uncertainty. Negotiation is used to transform perceived challenges of uncertainty into feelings of competence in relation to (the prevention of) food allergy. Core themes included ‘parental roles’, ‘healthcare’, ‘childcare’, ‘informal support’ and ‘family routines’. To cope with the challenges, parents relied on two main resources: self-efficacy and health literacy.Conclusion The study highlights the dynamic process of negotiation within families at risk of or coping with paediatric food allergy. Furthermore, our findings highlight the need to promote parental health literacy.